Charts for calculation of the critical stress for local instability of columns with I-, Z-, channel, and rectangular-tube section - Kroll, W. D. (National Advisory Committee for Aeronautics, 1943)
Charts are presented for the calculation of the critical stress for local instability of columns with I-, Z-, channel, and rectangular-tube section. These charts are intended to replace the less complete charts published in NACA Technical Note No. 743. The values used in extending the charts are computed by moment-distribution methods that give somewhat more accurate values than the energy method previously used and also make it possible to determine theoretically which element of the cross section is primarily responsible for instability.
NACA Wartime Report L-429.
Originally issued as NACA as Advance Restricted Report L3K04 (November 1943).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Columns.; Aluminum alloys.; Loads (Mechanics); Strains and stresses.; Tubes.; Charts, diagrams, etc.; Pipe.; elektronické knihy; electronic books